(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article presents the results of many years of research into the introduction of 21 species of rare and endemic tulips from Kazakhstan’s flora in four Botanical Gardens in Kazakhstan, Kyrgyzstan and Ukraine. A comparative assessment of the timing of flowering, morphological variability, and success of introduction was carried out, and the most promising species for each region were identified. The first place among them is occupied by Tulipa tarda Stapf, which fully naturalizes in three regions of the study, with the exception of the desert Zhezkazgan.